1997
DOI: 10.1159/000289104
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Major Depression in End-Stage Renal Disease

Abstract: Background: Although major depression commonly occurs in medically ill patients, it can be difficult to diagnose since depression and many medical illnesses share common physical symptoms. Methods: This study was designed to evaluate patients with end-stage renal disease (ESRD) for major depressive disorder using three diagnostic approaches, to assess the Beck Depression Inventory as a screening instrument for major depression, and to examine the association of anhedonia with a diagnosis of major depression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 7 publications
(8 reference statements)
2
23
0
1
Order By: Relevance
“…The BDI scores observed in our population (mean = 16.2 ± 10.6 and median = 14) fell within the range defined as mild depression by Beck et al, 12 and were similar to the scores reported by other investigators. [21][22][23] The choice of a cutoff of 14 for the BDI score was mainly related to obtaining two groups with similar samples sizes, no intention to establish a particular level to be used for BDI. Instead, this choice was focused on creating two distinct groups, one with less intense depressive symptoms and the other with more intense symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The BDI scores observed in our population (mean = 16.2 ± 10.6 and median = 14) fell within the range defined as mild depression by Beck et al, 12 and were similar to the scores reported by other investigators. [21][22][23] The choice of a cutoff of 14 for the BDI score was mainly related to obtaining two groups with similar samples sizes, no intention to establish a particular level to be used for BDI. Instead, this choice was focused on creating two distinct groups, one with less intense depressive symptoms and the other with more intense symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The second edition of the Beck Depression Inventory-II (BDI-II) [28] was used to assess the level of depressive symptoms. The BDI is the most popular self-reporting tool for measuring depressive symptoms and has often been used to evaluate mental health in ESRD patients [29]. It was revised to correspond to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, criteria and was published as the BDI-II in 1996.…”
Section: Methodsmentioning
confidence: 99%
“…To address the need for brief assessment tools for health professionals who perceive that they have limited time to conduct evaluations, O'Donnell and Chung (42) evaluated the use of very brief screening questions in the assessment of depression. These studies have shown that one-or two-question assessments, focusing on the core symptom of depressed mood or anhedonia, can prove useful in the medically ill (42).…”
Section: Diagnosismentioning
confidence: 99%